The Other Obesity Epidemic—Of Drugs and Bugs - Sfera, Adonis; Osorio, Carolina; Diaz, Eddie Lee; Maguire, Gerald; Cummings, Michael (Frontiers in Endocrinology, 2020)
Chronic psychiatric patients with schizophrenia and related disorders are frequently treatment-resistant and may require higher doses of psychotropic drugs to remain stable. Prolonged exposure to these agents increases the risk of weight gain and cardiometabolic disorders, leading to poorer outcomes and higher medical cost. It is well established that obesity has reached epidemic proportions throughout the world, however it is less known that its rates are two to three times higher in mentally ill patients compared to the general population. Psychotropic drugs have emerged as a major cause of weight gain, pointing to an urgent need for novel interventions to attenuate this unintended consequence. Recently, the gut microbial community has been linked to psychotropic drugs-induced obesity as these agents were found to possess antimicrobial properties and trigger intestinal dysbiosis, depleting Bacteroidetes phylum. Since germ-free animals exposed to psychotropics have not demonstrated weight gain, altered commensal flora composition is believed to be necessary and sufficient to induce dysmetabolism. Conversely, not only do psychotropics disrupt the composition of gut microbiota but the later alter the metabolism of the former. Here we review the role of gut bacterial community in psychotropic drugs metabolism and dysbiosis. We discuss potential biomarkers reflecting the status of Bacteroidetes phylum and take a closer look at nutritional interventions, fecal microbiota transplantation and transcranial magnetic stimulation, strategies that may lower obesity rates in chronic psychiatric patients.